Feasibility of Extracting Meaningful Patient Centered Outcomes From the Electronic Health Record Following Critical Illness in the Elderly - Ahmad, Sumera R.; Tarabochia, Alex D.; Budahn, Luann; Lemahieu, Allison M.; Anderson, Brenda; Vashistha, Kirtivardhan; Karnatovskaia, Lioudmila; Gajic, Ognjen (Frontiers in Medicine, 2022)
Background: Meaningful patient centered outcomes of critical illness such as functional status, cognition and mental health are studied using validated measurement tools that may often be impractical outside research setting. Electronic health record (EHR) contains a plethora of information pertaining to these domains. We sought to determine how feasible and reliable it is to assess meaningful patient centered outcomes from the EHR. Methods: Two independent investigators reviewed EHR of a random sample of ICU patients looking at documented assessments of trajectory of functional status, cognition, and mental health. Cohen’s kappa was used to measure agreement between 2 reviewers. Post ICU health in these domains 12 month after admission was compared to pre- ICU health in the 12 months prior to assess qualitatively, if patient’s condition is ‘better’, ‘unchanged’ or ‘worse’. Days alive and out of hospital/health care facility, was a secondary outcome. Results: Thirty six of the 41 randomly selected patients (88%) survived critical illness. In majority of survivors (86%) EHR contained sufficient information to determine the difference in health status before and after critical illness. Decline in functional status (36%), cognition (11%), and mental health (11%) following ICU admission was observed compared to premorbid baseline. Agreement between reviewers was excellent (kappa ranging from 0.966 to 1). Eighteen patients (44%) remained home after discharge from hospital and rehabilitation during the 12- month follow up. Conclusion: We demonstrated feasibility and reliability of assessing trajectory of changes in functional status, cognition, and selected mental health outcomes, from EHR of critically ill patients. If validated in a larger, representative sample, these outcomes can be used alongside survival in quality improvement studies and pragmatic clinical trials.